Risk factors of cerebral palsy in children, patterns and associated troubles - Suliman, Suzan Mahmoud; Ghalia, Mazen; Chreitah, Ahmad (Journal of medical and pharmaceutical sciences, 2022)
Introduction: Cerebral palsy is the most common neurological disorder seen in childhood, and part of chronic diseases at this stage, which poses a great social and economic challenge at the family level, medical staff and rehabilitation centers. To assess the actual needs for patient management in various fields, it was necessary to study the problem at the local level. The main objectives: To study the risk factors associated with cerebral palsy in children attending the Neurological Clinic in Tishreen University Hospital. Materials and methods: The study included all children diagnosed with cerebral palsy up to the age of 14 who attended the Neurology Clinic at Tishreen University Hospital during the study period from May 2020 to June 2021. Data were analyzed according to: gender distribution, age of the injured, method of delivery, and the age at which the child first attended the clinic. In addition to studying potential risk factors during pregnancy, and causes in the perinatal and postpartum period. Cerebral palsy was stereotyped and the degree of disability was determined based on the clinical examination and the need for aids. The accompanying disorders and the various complaints that these children were referred to were recorded and included in categories. The diagnosis was based on clinical examination, pathological history, radiological investigations and available laboratory analyzes. Results: The sample included 163 children with a male preponderance of 68%. In the research sample, there was a relationship between the parents of 40 children at a rate of 24.5%. The risk factors that were found in the mothers of the children were sepsis during pregnancy, diabetes and preeclampsia. The form of perinatal asphyxia was the most dangerous perinatal factor seen and there was no differences in the method of delivery. The most causative factor after birth is the need for oxygen or a ventilator. Delayed milestone, speech delay, and convulsions constituted the most associated troubles. The spastic pattern is the most frequently seen pattern. As for the applied procedures, the most common was CT scan with 71.8.